2014
DOI: 10.1016/j.egypro.2014.07.045
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Pipeline Integrity: Comparison of a Coupled Fluid-structure Model and Uncoupled Two-curve Methods

Abstract: One challenge in CCS is related to the prevention of running-ductile fracture in CO 2 -carrying pipelines. Commonly used tools for ensuring crack arrest in pipelines hinge mainly on semi-empirical models, which may not be appropriate for CO 2 transport since they have been developed and fitted for natural gas and older pipeline materials, and due to an assumed decoupling of the fluid decompression and fracture propagation phenomena. In this paper, we apply a coupled fluid-structure model to a case with pure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It has been found that a pipeline transporting CO 2 will be more susceptible to running-ductile fracture than one carrying natural gas (Mahgerefteh et al, 2012;Aursand et al, 2014). One part of the design to avoid running-ductile fracture necessitates accurate models predicting the depressurization behaviour of the relevant CO 2 -rich mixtures, noting that existing semi-empirical models have been deemed not to be directly applicable to CO 2 pipelines (Jones et al, 2013).…”
Section: Nomenclaturementioning
confidence: 99%
“…It has been found that a pipeline transporting CO 2 will be more susceptible to running-ductile fracture than one carrying natural gas (Mahgerefteh et al, 2012;Aursand et al, 2014). One part of the design to avoid running-ductile fracture necessitates accurate models predicting the depressurization behaviour of the relevant CO 2 -rich mixtures, noting that existing semi-empirical models have been deemed not to be directly applicable to CO 2 pipelines (Jones et al, 2013).…”
Section: Nomenclaturementioning
confidence: 99%
“…A two-way coupling between these two parts is implemented. This coupled fluid-structure model has been validated against crack-arrest experiments performed with methane and hydrogen [15,32], and it has later been extended to accurately account for two-phase (gas-liquid) and three-phase (gas-liquid-solid) CO 2 [13,33,34,35]. In the present work, the model is extended with an improved method to estimate the circumferentially varying pressure load on the fracture flaps, and a backfill model is employed to represent the material surrounding the pipe.…”
Section: Existing Fpc Methods For Pipelinesmentioning
confidence: 99%
“…Following our earlier work [13,35], we model the one-dimensional compressible flow of pure CO 2 using the homogeneous equilibrium model and the Span-Wagner [57] reference equation of state (EOS). The flow model may be written as…”
Section: Fluid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently several authors have developed methodologies to couple pipeline outflow and crack propagation models (Greenshields et al, 2000;Aursand et al, 2014;Mahgerefteh et al, 2012;Nordhagen et al, 2012). These methodologies are largely based on the Homogenous Equilibrium Mixture (HEM) model of pipe flow and utilise various models describing the pipe wall rupture, ranging from HLP-type models (Makino et al, 2001;Mahgerefteh et al, 2012) to FEM models accounting for ductile fracture of elasto-plastic material (Aursand et al, 2014). While the above studies have been focused on simulation of ductile fractures, modelling of the brittle mode of pipeline failure has not received as much attention yet.…”
Section: Introductionmentioning
confidence: 99%